Design of Chip Conveyor - Szabó, Kristóf (International Journal of Engineering and Management Sciences, 2020)
The following article examines the design methodology of screw conveyors. The most significant steps are discussed concerning the design of the apparatus and its use in machine tools as a service component is explained.